Survey of web sites in relation to customer resource life cycle and nature of products. - Chua, Choong Thoong. (2008)
Survey on websites of Australia, USA, Singapore and Malaysia by industry. The sites selected are then put into the types of goods they provide and then data is collected. From the data, we put them into the stages of our modified Customer Resource Life Cycle and then we analyse the data. We then find differences among websites that have been classified according to sectors and country and analyse them.